Development of thermally conductive polymer matrix composites by foaming‐assisted networking of micron‐ and submicron‐scale hexagonal boron nitride. Issue 4 (26th September 2015) - Ding, Hao; Guo, Yanting; Leung, Siu Ning
ABSTRACT: Thermally conductive polymer matrix composite (PMC) foams with effective thermal conductivities ( k eff ) higher than their solid counterparts have been developed for the first time. Using a material system consists of low density polyethylene and micron‐scale or submicron‐scale hexagon boron nitride platelets as a case example, this article demonstrates that foaming‐assisted filler networking is a feasible processing strategy to enhance PMC's k eff, especially at a low hBN loading. Parametric studies were conducted to identify the structure‐to‐property relationships between foam morphology (e.g., cell population density, cell size, and foam expansion) and the PMC foam's k eff . In particular, there exists an optimal cell size to maximize the PMC foam's k eff for foams with up to 50% volume expansion. However, an optimal cell size is absent for PMC foams with higher volume expansion. X‐ray diffraction (XRD) analyses reveal that both the presence of hBN platelets and foam expansion promoted the crystallization of LDPE phase. Moreover, the XRD spectra also provide evidence for the effect of foam expansion on the orientation of hBN platelets. Overall, the findings provide new directions to design and fabricate thermally conductive PMC foams with low filler contents for heat management applications. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42910. Abstract :